Molecular regulation and function of FoxO3 in chronic kidney disease. Issue 4 (July 2020) - Lin, Fangming
Abstract : Purpose of review: FOXOs are transcription factors that regulate downstream target genes to counteract to cell stress. Here we review the function and regulation of FOXO transcription factors, the mechanism of FOXO3 activation in the kidney, and the role of FOXO3 in delaying the development of chronic kidney disease (CKD). Recent findings: Progressive renal hypoxia from vascular dropout and metabolic perturbation is a pathogenic factor for the initiation and development of CKD. Hypoxia and low levels of α-ketoglutarate generated from the TCA cycle inhibit prolyl hydroxylase domain (PHD)-mediated prolyl hydroxylation of FoxO3, thus reducing FoxO3 protein degradation via the ubiquitin proteasomal pathway, similar to HIF stabilization under hypoxic conditions. FoxO3 accumulation and nuclear translocation activate two key cellular defense mechanisms, autophagy and antioxidative response in renal tubular cells, to reduce cell injury and promote cell survival. FoxO3 directly activates the expression of Atg proteins, which replenishes core components of the autophagic machinery to allow sustained autophagy in the chronically hypoxic kidney. FoxO3 protects mitochondria by stimulating the expression of superoxide dismutase 2 (SOD2), as tubular deletion of FoxO3 in mice results in reduced SOD2 levels and profound mitochondrial damage. Summary: Knowledge gained from animal studies may help understand the function of stress responsive transcription factors that could be targeted to prevent or treat CKD.